Security and Satisfaction: The Twin Pillars of Sustainable Employee Loyalty in Indonesia - Melania Melania; Meiske Kristin Lumanauw (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study examines how Career Development, Work-Life Balance, Organizational Culture, and Job Security shape Employee Satisfaction, and how that satisfaction, in turn, influences Employee Loyalty among employees in conventional banks in Indonesia. Using a quantitative approach, the findings indicate that all four factors play an important role in enhancing employee satisfaction, with organizational culture emerging as the most influential aspect. The study also confirms that employees who feel satisfied with their work environment tend to show stronger loyalty and commitment to their organizations. These results underscore the need for banking institutions to foster supportive cultures, provide clear career pathways, and strengthen job stability to improve employee engagement and retention. The insights presented in this research offer valuable guidance for HR practitioners in designing effective strategies to build a committed and satisfied workforce.